Nonsyndromic cleft lip with or without cleft palate: Increased burden of rare variants within Gremlin‐1, a component of the bone morphogenetic protein 4 pathway. Issue 6 (7th April 2014) - Al Chawa, Taofik; Ludwig, Kerstin U.; Fier, Heide; Pötzsch, Bernd; Reich, Rudolf H.; Schmidt, Gül; Braumann, Bert; Daratsianos, Nikolaos; Böhmer, Anne C.; Schuencke, Hannah; Alblas, Margrieta; Fricker, Nadine; et al.
<x xml:space="preserve">Abstract</x> Background The genes Gremlin‐1 (GREM1) and Noggin (NOG) are components of the bone morphogenetic protein 4 pathway, which has been implicated in craniofacial development. Both genes map to recently identified susceptibility loci (chromosomal region 15q13, 17q22) for nonsyndromic cleft lip with or without cleft palate (nsCL/P). The aim of the present study was to determine whether rare variants in either gene are implicated in nsCL/P etiology. Methods The complete coding regions, untranslated regions, and splice sites of GREM1 and NOG were sequenced in 96 nsCL/P patients and 96 controls of Central European ethnicity. Three burden and four nonburden tests were performed. Statistically significant results were followed up in a second case‐control sample (n = 96, respectively). For rare variants observed in cases, segregation analyses were performed. Results In NOG, four rare sequence variants (minor allele frequency < 1%) were identified. Here, burden and nonburden analyses generated nonsignificant results. In GREM1, 33 variants were identified, 15 of which were rare. Of these, five were novel. Significant p‐values were generated in three nonburden analyses. Segregation analyses revealed incomplete penetrance for all variants investigated. Conclusion Our study did not provide support for NOG being the causal gene at 17q22. However, the observation of a significant excess of rare variants in GREM1 supports the hypothesis that this is the causal gene at chr. 15q13. Because no single causal variant was identified, future sequencing analyses of GREM1 should involve larger samples and the investigation of regulatory elements. Birth Defects Research (Part A) 100:493–498, 2014. © 2014 Wiley Periodicals, Inc.